ANALISIS PENYALURAN KREDIT MODAL KERJA PADA BANK UMUM DI INDONESIA - Vebian Indriati; Idah Zuhroh; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2018)
This study aims to describe the development of Third Party Funds (DPK), Lending Rates (SBK), Non Performing Loan (NPL) and loan portfolio of working capital as well as to analyze the influence of Third Party Funds, Interest Rates, Non Performing Loan to lending working capital commercial banks in Indonesia in 2012-2016. Data analysis technique used is the panel data regression analyzes were then performed hypothesis testing by F test, t test, and the coefficient of determination (R²) at a significance level α = 5%. The results showed that the variables simultaneously DPK, SBK and NPL effect on working capital loans. While partially, DPK variable positive and significant impact, SBK negative and significant effect, and NPL negative and not significant to the working capital loans at commercial banks in Indonesia. The coefficient of determination (R²) is 0.7569 or 75.69%. This indicates that the variable DPK, SBK and NPL able to explain the variable lending working capital amounted to 75.69%.Keywords : Third Party Funds, Interest Rates, Non-Performing Loans, Working Capital Loans